The Summer Place : a novel - Weiner, Jennifer (New York : Atria Books, 2022)
At her stepdaughter's wedding day to her pandemic boyfriend--the last gathering at the family's beach house in Cape Cod--Sarah is faced with lovers being revealed as their true selves, misunderstandings, and secrets, ensuring that nothing will ever be thesame.
new book 2022 spring.
Keywords: Weddings -- Fiction; Families -- Fiction; Cape Cod (Mass.) -- Fiction; Novels